THE EFFECT OF PERCEIVED EASE OF USE, PERCEIVED USEFULNESS, TRUST, CUSTOMER SATISFACTION AND ONLINE PAYMENT REUSE INTENTION (CASE STUDY IN OVO APPLICATION USER PONTIANAK) - Admin, ALBER SEAN SIMBOLON B1024161008 (Jurnal Manajemen Update, 2020)
ABSTRACTThe purpose of this research evaluation is to analyze the effect of perceived ease of use, perceived usefulness, trust, customer satisfaction and intention to reuse online payments in Pontianak. In current technological developments or better known as the 4.0 era. In the complex, namely in the world of business, politics, social and education. This research is a quantitative study using a survey method with a questionnaire as a tool to obtain data. Questionnaires were given to 100 samples that met the requirements. In this case my research target was adults in Pontianak who were invited for a minimum of 17 years. This study uses a data analysis model of partial least square structural equations (SEMPLS). To conduct the analysis using the PLS method, this study uses a smartPLS 3.0 data testing machine. The hypothesis of this study is H1: perceived ease of use has a significant effect on online payment reuse intentions, H2: perceived benefits of online payment reuse intentions, H3: trust in online payment reuse intentions and H4: customer satisfaction with repayment intention on line. The results of this study prove that H1, H2, H3 and H4 were accepted.Key word: Perceived Ease of Use, Perceived Usefulness, Trust, customer satisfaction and Online payment reuse intentionÂ Â Â Â Â Â  Â Â Â Â Â Â References(Al-Mamary, Al-nashmi, Hassan, & Shamsuddin, 2016). A Critical ReviewÂ Â Â Â Â Â Â Â Â Â Â  of Models and Theories in Field of Individual Acceptance of TechnologyÂ Â Â Â Â Â Â Â Â  VOL. 9. No.6 (2016). Pp. 143-158Â Alreck.P& R.Settle (2004), Survey Research Handbook (third ed.), McGraw Hill, New York,NYAnderson, E., and Weitz, B. (1989). Determinants of Continuity in ConventionalÂ Â  Industrial Channel Dyads. Marketing Science, 8 (4), 310-323. Â Anderson, J. C., and Gerbig, D. W. (1988). Structural Equation Modeling inÂ Â Â Â Â Â Â Â Â  Practice: A Review and Recommended Two-Step Approach. Psychological Bulletin, 103,Â Â  411-423.Anderson, R. E., & Srinivasan, S. S. (2003). E-Satisfaction and E-Loyalty: AÂ Â Â Â Â Â Â Â  ContingencyÂ Â Â  Framework. Psychology & Marketing, 20(2), 123-138,Â Â Â Â  doi:10.1002/mar.10063.Anderson, J. C., and Narus, J. A. (1990). A Model of Distributor Firm and ManufacturerÂ  Firm Working Partnerships. Journal of Marketing, 54 (1),Â Â Â Â  42-58.Asyraf Afthanorhan. (2017). Review on Partial Least Square Structural EquationÂ Â  Modeling (PLS-SEM) using SmartPLS 2.0Aulakh, P. S., Kotabe, M., and Arvind, S. (1996). Trust and Performance in Cross Border Marketing Partnerships: A Behavioural Approach. Journal ofÂ Â Â Â  InternationalÂ Â Â  BusinessBank Indonesia. (2014). Jumlah Uang Elektronik yang Beredar. www.bi.go.id.Â Â Â Â Â  Diakses pada 15 Mei 2015.Bhuvanesh Kumar Sharma, Vimal Bhatt (2018). Impact of Social Media onÂ Â Â Â Â Â Â Â Â Â  Consumer Buying Behavior â€“ A Descriptive Study on TAM Model inÂ Â Â Â Â  Journal of Management 13(1) â€¢ August 2018â€‚Bonoma, T. (1976). Conflict, Cooperation and Trust in Three PowerÂ Â Â Â Â Â Â Â Â Â  Systems.Behavioral Science, 21 (November), 499-514.Bradach, J. L., and Eccles, R. G. (1989). Price, Authority, and Trust: From IdealÂ Â  Types to Plural Forms. Annual Review of Sociology, 15, 97-118.Brian Whitworth, Edward Mahinda (2005). The Web of System Performance:Â Â Â Â Â Â  Extending the TAM Model. 11th Americas Conference on InformationÂ Â Â  Systems, AMCIS 2005, Omaha, Nebraska, USA, August 11-14, 2005Brown, Tom J and Peter A. Dacin. The Company and The Product: CorporateÂ Â Â Â Â Â  associations and Consumer 6 Product Responses. Journal of marketingÂ Â Â  Vol.61 (2005).F. D. Davis, â€œPerceived usefulness,perceived ease of use, and useracceptance of information technology,â€MIS Q., pp. 319â€“340, 1989F. D. Davis, â€œPerceived usefulness,perceived ease of use, and useracceptance of information technology,â€MIS Q., pp. 319â€“340, 1989F. D. Davis, â€œPerceived usefulness,perceived ease of use, and useracceptance of information technology,â€MIS Q., pp. 319â€“340, 1989F. D. Davis, â€œPerceived usefulness,perceived ease of use, and useracceptance of information technology,â€MIS Q., pp. 319â€“340, 1989Chuttur M.Y., 2009, "Overview of the Technology Acceptance Model: Origins,Â Â Â Â  Developments sand Future Directions," Indiana University, USA. Sprouts:Â Â Â Â Â Â Â Â  Working Papers on Information Systems, 9(37). http://sprouts.aisnet.org/9Â Â Â Â Â Â Â  37Davis, F.D. (1993) â€œUser Acceptance of Information Technology SystemÂ Â  Characteristics, User Perceptions and Behavioral Impactsâ€ InternationalÂ Â Â Â Â Â Â Â Â Â  Journal of Man-Machine Studies 38(3), pp. 475-487.Â Davis, F.D., R.P. Bagozzi, and P.R. Warshaw (1989) â€œUser Acceptance of Computer Technology: A Comparison of Two Theoretical Modelsâ€Â Â Â Â Â Â  Management Science 35(8), pp.982-1003.Â Davis, F.D., R.P. Bagozzi, and P.R. Warshaw (1992) â€œExtrinsic and IntrinsicÂ Â Â Â Â Â Â Â  Motivation to Use Computers in the Workplaceâ€ Journal of Applied SocialÂ Â Â Â Â Â  Psychology 22(14), pp.1111-1132.Davis, F.D., and V. Venkatesh (1996) â€œA Critical Assessment of Potential Measurement Biases in the Technology Acceptance Model: ThreeÂ Â Â Â Â Â Â Â Â Â  Experimentsâ€ International Journal of Human-Computer Studies 45(1),Â Â  pp.19-45.Devi, Ni Luh Nyoman Sherina dan Suartana, I Wayan. 2014. Analisis Technology Acceptance Model (Tam) Terhadap Penggunaan Sistem Informasi Di NusaÂ Â Â Â Â  Dua Beach Hotel & Spa. EJurnal Akuntansi Universitas Udayana 6.1Â Â Â  (2014): 167-184 ISSN: 2302-8556.DeLone, W. H., & McLean, E. R. (2003). The Delone and Mclean model of information systemssuccess: A ten-year update. Journal of Management Information Systems, 19(4), 9â€“30.DeLone, W. H., & McLean, E. R. (2003). The Delone and Mclean model of information systemssuccess: A ten-year update. Journal of Management Information Systems, 19(4), 9â€“30.DeLone, W. H., & McLean, E. R. (2003). The Delone and Mclean model of information systemssuccess: A ten-year update. Journal of Management Information Systems, 19(4), 9â€“30.DeLone, W. H., & McLean, E. R. (2003). The Delone and Mclean model of information systemssuccess: A ten-year update. Journal of Management Information Systems, 19(4), 9â€“30.DeLone, W. H., & McLean, E. R. (2003). The Delone and Mclean model of information systemssuccess: A ten-year update. Journal of Management Information Systems, 19(4), 9â€“30.DeLone, W. H., & McLean, E. R. (2003). The Delone and Mclean model of information systemssuccess: A ten-year update. Journal of Management Information Systems, 19(4), 9â€“30.DeLone, W. H., & McLean, E. R. (2003). The Delone and Mclean model of information systemssuccess: A ten-year update. Journal of Management Information Systems, 19(4), 9â€“30.DeLone, W. H., & McLean, E. R. (2003). The Delone and Mclean model of information systemssuccess: A ten-year update. Journal of Management Information Systems, 19(4), 9â€“30.DeLone, W. H., & McLean, E. R. (2003). The Delone and Mclean model of information systemssuccess: A ten-year update. Journal of Management Information Systems, 19(4), 9â€“30.DeLone, W. H., & McLean, E. R. (2003). The Delone and Mclean model of information systemssuccess: A ten-year update. Journal of Management Information Systems, 19(4), 9â€“30.DeLone, W. H., & McLean, E. R. (2003). The Delone and Mclean model of information systemssuccess: A ten-year update. Journal of Management Information Systems, 19(4), 9â€“30.DeLone WH, McLean ER (2003) The DeLone and McLean model of information systems success: a ten-year update. Journal of Management Information Systems 19(4):9â€“30Doll, W. J., and Torkzadeh, G. 1988. "The Measurement of End User Computing Satisfaction,"MIS Quarterly (12:2), June, pp. 259-274.Doll, W. J., and Torkzadeh, G. 1988. "The Measurement of End User Computing Satisfaction,"MIS Quarterly (12:2), June, pp. 259-274.Doll, W. J., & Torkzadeh, G. (1988). The measurement of end-user computingÂ Â Â Â Â Â  satisfaction. MIS quarterly, 259-274.Emi Amelia, 2019 ANALISIS PERILAKU MINAT MENGGUNAKAN MOBILEÂ Â Â Â Â Â Â Â  PAYMENT DENGAN PENDEKATAN TECHNOLOGY ACCEPTANCEÂ Â Â Â  MODEL 3Fishbein, M. and Ajzen, I. 1975. "Belief, Attitude, Intention and Behavior: AnÂ Â Â Â Â  Introduction to Theory and Research," Addison-Wesley, Reading, MAGao, L. and Bai, X. (2014), "A unified perspective on the factors influencingÂ Â Â Â Â Â Â Â  consumer acceptance of internet of things technology", Asia PacificÂ Â  Journal of Marketing and Logistics, Vol. 26 No. 2, pp. 211-231. Â Â Â Â Â Â Â Â Â Â Â Gefen, D., 2002. Customer Loyalty in E-Commerce, Journal of the Association forÂ Â Â Â Â Â Â Â Â Â Â  Information Systems, 3:27-51.Geyskens, I., Steenkamp, J. E. M., and Kumar, N. (1998). Generalizations aboutÂ Â Â  Trust in Marketing Channel Relationships Using Meta-analysis.Â Â Â  International Journal of Research in Marketing, 15(3), 223-248Gupta, R., & Kabadayi, S. (2010). The relationship between trusting beliefs andÂ Â Â  web site loyalty: the moderating role of consumer motives and flow.Â Â Â Â Â Â Â  Psychology & Marketing, 27(2), 166-185, doi:10.1002/mar.20325.Hair J. F., Hult G. T. M., Ringle C. M., Sarstedt M. (2014).Â A Primer on PartialÂ Â Â Â Â  Least Squares Structural Equation Modeling (PLS-SEM). Thousand Oaks:Â Â Â Â  Sage.Â Â Â Â Â Â Â Â Â Â Â  Henry. (2011, August 24). Path Analysis with LISREL (Chapter 1). Retrieved fromÂ Â Â Â Â Â Â Â Â Â Â  Teori Online: https://teorionline.wordpress.com/2011/08/24/path-analysisÂ  with-lisrel chapter-1/Holmbeck (1997,p.599). Toward terminological, conceptual, and statistical clarityÂ  in the study of mediators and moderators: Examples from the childÂ Â Â Â Â  clinical and pediatric psychology literatures. Journal of Consulting and ClinicalÂ Â Â Â  Psychology. 1997;65:599â€“610.https://www.statista.com/outlook/243/120/ecommerce/indonesiaInternational Journal of Hybrid Information TechnologyVol. 9, No.6 (2016), pp. 143-158http://dx.doi.org/10.14257/ijhit.2016.9.6.13International Journal of Hybrid Information TechnologyVol. 9, No.6 (2016), pp. 143-158http://dx.doi.org/10.14257/ijhit.2016.9.6.13International Journal of Hybrid Information TechnologyVol. 9, No.6 (2016), pp. 143-158http://dx.doi.org/10.14257/ijhit.2016.9.6.13International Journal of Hybrid Information TechnologyVol. 9, No.6 (2016), pp. 143-158http://dx.doi.org/10.14257/ijhit.2016.9.6.13International Journal of Hybrid Information TechnologyVol. 9, No.6 (2016), pp. 143-158http://dx.doi.org/10.14257/ijhit.2016.9.6.13International Journal of Hybrid Information TechnologyVol. 9, No.6 (2016), pp. 143-158http://dx.doi.org/10.14257/ijhit.2016.9.6.13https://www.indonesia-investments.com/id/news/todays-headlines/mckinsey-expectsÂ Â Â Â Â Â Â Â  great-growth-for-indonesia-s-e-commerce-market/item8959?https://theaseanpost.com/article/rise-e-commerce-indonesia.Kuciapski, M. (2017), "A model of mobile technologies acceptance for knowledge transfer by employees", Journal of Knowledge Management, Vol. 21 No. 5,Â  pp.1053-1076.Kotler, P., & Gertner, D. (2002). Theoretical papers. Country as brand, product, andÂ Â Â Â Â Â Â Â Â  beyond: A place marketing and brand management perspective. Journal ofÂ Â Â Â  Brand Management, 9 (4-5), 249-261.Kotler, P., Hamlin, M.A., Rein, I., & Haider, D.H. (2002). Marketing Asian Places.Â Â Â Â Â Â Â Â Â Â  Singapore: John Wiley & Sons.Kotler, P. and K. Kelvin, (2006). Marketing management. 12th Edn., New Jersey: Â Â Â Â Â Â Â Â Â Â Â  Pearson Education Inc.Kotler and Keller (2016). The holistic marketing concept is based on theÂ Â Â Â  development,Â  design, and implementation of marketing programs,Â Â Â Â Â Â Â Â  processes, and activities thatÂ Â  recognize their breadth andÂ Â Â Â Â Â Â Â Â Â Â  interdependencies.Koufaris, M. (2002). Applying the technology acceptance model and flow theoryÂ  to online consumer behavior. Information Systems Research, 13(2),Â Â Â Â Â Â Â  205223, doi:10.1287/isre.13.2.205.83. 158.Luarn, P., & Lin, H.-H. (2005). Toward an understanding of the behavioralÂ Â Â Â Â Â Â Â Â Â Â  intention to use mobile banking. Computers in Human Behavior, 21(6),873Â  891.Lupioyadi, R. 2001. Manajemen Pemasaran Jasa: Teori dan Praktek (ServiceÂ Â Â Â Â Â Â Â Â  Marketing Management: Theory and Practice)Lau, G. T. dan Lee, S. H., 1999, Consumersâ€™ trust in a brand and the link to brand loyalty, Journal of Market Focused Management, Vol 4: 341-370Malhotra, N. (2013). Marketing research. Upper Saddle River: Pearson PrenticeÂ Â Â Â  Hall. Intl.Â Â Â Â Â Â Â Â Â Â Â  Malhotra, N. K. (2010). Marketing Research : An Applied Orientation sixth edition.Â Â Â Â Â Â Â Â Â Â Â  PEARSON EDUCATION.Margianto,H. (2014, August 30). Kompas. Retrieved from Kompas.com: https://ekonomi.kompas.com/read/2014/08/30/204444826/.Cashless.Sociey.Ketika.Uang.Fisik.Hilang.dari.Dompet.AndaMayer, R.C., Davis, J. H., dan Schoorman, F.D., (1995), An Integratif Model ofÂ Â Â  Organizational Trust,Â  Academy of Management Review, 30 (3): 709-734McKinsey (30 Agustus 2018) The Digital Archipelago: How Online Commerce is Driving Indonesia's Economic DevelopmentÂ Â Â Â Â Â Â Â Â Â Â  Merriam-Webster. (2018). Merriam-Webster: Questionnaire. Retrieved fromÂ Â Â Â Â Â Â Â Â Â Â  https://www.merriamebster.com/dictionary/questionnaireMorgan and Hunt (1994). The Commitment-Trust Theory of RelationshipÂ Â  Marketing. Journal of Marketing 58(3):20-38Mowen, John, C., and Minor, M. 2002. Perilaku Konsumen Jilid 1, Edisi KelimaÂ Â Â  (translation), Erlangga, JakartaMuhammad Hassan, Syed Sibtain Ali Shah Kazmi, Siti Falindah Padlee (2019).Â Â Â Â  Technology Acceptance Model (TAM) and Dynamics of Online PurchaseÂ Â Â Â Â  Adaptability, 29 July 2019, Malaysia.Murphy, G.Â  B. and Blessinger, A. A. 2003. â€œPerceptions of No-name RecognitionÂ Â Â Â Â Â Â Â Â Â Â  Business to Consumer E-Commerce Trustworthiness: The Effectiveness ofÂ Â Â Â Â Â Â  Potential Influence Tactics,â€ Journal of High Technology ManagementÂ Â Â Â Â Â Â Â Â Â  Research (14), pp 71-92.Riegelsberger,Â  J.,Â  Sasse,Â  M.Â  A.,Â  andÂ  McCarthy,Â  J. D.Â  2003.Â  â€œTheÂ  Researcerâ€™sMukherjee, A., dan Nath, P., (2003), A Model of Trust in Online RelationshipÂ Â Â Â Â Â  Banking, International Journal of Bank Marketing, 21 (1): 5-15.Â Â Pavlou, Paul A., dan D. Gefen. (2002). Building Effective Online MarketplacesÂ Â Â Â  with Institution-based Trust. Proceedings of Twenty-Third InternationalÂ Â Â Â  Conference on Information Systems. pp. 667-675.Â Â Â Pavlou, P.A. (2003), â€œConsumer acceptance of electronic commerce: integratingÂ Â Â  trust and risk with the technology acceptance modelâ€, International JournalÂ Â Â Â Â Â Â Â Â Â Â  of Electronic Commerce, Vol. 7 No. 3, pp. 69-103.Pipitwanichakarn, T. and Wongtada, N. (2019),"Leveraging the technologyÂ Â Â Â Â Â Â Â Â Â Â  acceptance model for mobile commerce adoption under distinct stages ofÂ  adoption", Asia Pacific Journal of Marketing and LogisticsPinem, A., Immanuella, I., Hidayanto, A., Phusavat,K. and, M. (2018), "Trust and its impact towards continuance of use in government-to-business online service", Transforming Government: People, Process and Policy, Vol. 12Â Â Â Â Â Â Â Â Â Â Â  No. 3/4, pp. 265285.Ramayah, T. & Lo, M.-C. (2007). Impact of shared beliefs on â€œperceivedÂ Â  usefulnessâ€ and â€œeaseÂ  ofÂ  useâ€Â  inÂ  the implementation of an enterpriseÂ Â Â  resource planning system.Surachman, A. (2013). Analysis of the Influence ofPerceived Usefulness, Perceived Ease of Use,Subjective Norm, Mobility, and Use Situation onIndividual Intention to Use M-Library.Â  ThesisSummery. Gadjah Mada UniversitySurachman, A. (2013). Analysis of the Influence ofPerceived Usefulness, Perceived Ease of Use,Subjective Norm, Mobility, and Use Situation onIndividual Intention to Use M-Library.Â  ThesisSummery. Gadjah Mada UniversitySurachman, A. (2013). Analysis of the Influence ofPerceived Usefulness, Perceived Ease of Use,Subjective Norm, Mobility, and Use Situation onIndividual Intention to Use M-Library.Â  ThesisSummery. Gadjah Mada UniversitySurachman, A. (2013). Analysis of the Influence ofPerceived Usefulness, Perceived Ease of Use,Subjective Norm, Mobility, and Use Situation onIndividual Intention to Use M-Library.Â  ThesisSummery. Gadjah Mada UniversityRamadan, R. and Aita, J. (2018), "A model of mobile payment usage among Arab consumers",Rangkuti.F. (2006). Riset Pemasaran. Jakarta : Gramedia Pustaka Utama.Riegelsberger, J., Sasse, M. A., and McCarthy, J. D. 2003. â€œThe Researcerâ€™sÂ Â Â Â Â Â Â Â Â Â  Dilemma: Evaluating Trust in Computer-Mediated Communication,â€Â Â Â Â Â  International Journal of Human-Computer Studies (58), pp 759-781.Roger C. Mayer, James H. Davis, F. David Schoorman Source: The Academy ofÂ Â  Management Review, Vol. 20, No. 3 (Jul., 1995), pp. 709-734SeppÃ¤nen, R., Blomqvist, K., and Sundqvist, S. (2007). Measuring Inter Â Â Â  organizationalÂ  Trust: A Critical Review of the Empirical Research in 1990 2003. IndustrialÂ  MarketingSheng, T. and Liu, C. (2010), "An empirical study on the effect of e servicequality on online customer satisfaction and loyalty", Nankai Business ReviewÂ Â Â  International,Â Â  Vol. 1 No. 3, pp. 273-283.Stone, M., Neil, W., Liz, M.Â Â  (2001). The art of marketing, (Vol.8). New Delhi:Â Â Â Â  Crest Publishing House.Â Surachman, A. (2013). Analysis of the Influence ofPerceived Usefulness, Perceived Ease of Use,Subjective Norm, Mobility, and Use Situation onIndividual Intention to Use M-Library.Â  ThesisSummery. Gadjah Mada UniversityManagement, 36 (2), 249-265.Research in Marketing, 15 (3), 223-248.Sugiyono, (2012). Statistics for Research. CV Alfabeta: Jakarta.Surachman, A. (2013). Analysis of the Influence ofPerceived Usefulness, Perceived Ease of Use,Subjective Norm, Mobility, and Use Situation onIndividual Intention to Use M-Library.Â  ThesisSummery. Gadjah Mada UniversitySurachman, A. (2013). Analysis of the Influence ofPerceived Usefulness, Perceived Ease of Use,Subjective Norm, Mobility, and Use Situation onIndividual Intention to Use M-Library.Â  ThesisSummery. Gadjah Mada UniversitySurachman, A. (2013). Analysis of the Influence ofPerceived Usefulness, Perceived Ease of Use,Subjective Norm, Mobility, and Use Situation onIndividual Intention to Use M-Library.Â  ThesisSummery. Gadjah Mada UniversitySurachman, A. (2013). Analysis of the Influence ofPerceived Usefulness, Perceived Ease of Use,Subjective Norm, Mobility, and Use Situation onIndividual Intention to Use M-Library.Â  ThesisSummery. Gadjah Mada UniversitySurachman (2013). ANALYSIS OF THE INFLUENCE OF PERCEIVEDÂ Â Â Â Â Â Â Â Â Â  USEFULNESS, PERCEIVED EASE OF USE, SUBJECTIVE NORM,Â Â Â Â Â Â  MOBILITY, AND USE SITUATION ON INDIVIDUAL INTENTION TOÂ Â Â Â Â  USE M-LIBRARY, DOI: 10.13140/2.1.2540.0006.Swanson RA, Chermack TJ (2013). Theory building in applied disciplines. Berrett Koehler Publishers.Venkatesh, Viswanath and Fred D. Davis. 2000. â€œA Theoretical Extension of theÂ  Technology Acceptance Model: Four Longitudinal Field Studiesâ€.Â Â Â Â  ManagementÂ Â  Science 46(2), pp 186- 204Venkatesh, V dan F.D. Davis. 1996. â€œA Model of The Antecendents of Perceived Ease ofÂ Â Â Â Â Â Â Â Â Â Â  Use Develompment dan Testâ€, Decision Science Vol. 27, h.451481.Wang, F., & Head, M. (2007). How can the Web help build customer relationships?Â Â Â Â Â Â Â Â Â  An empirical study on e-tailing. Information & Management, 44(2),Â Â Â Â Â Â Â  115129, doi:10.1016/j.im.2006.10.008Wang, X., Yu, C., & Wei, Y. (2012). Social media peer communication and impactsÂ Â Â Â Â Â Â Â Â  on purchase intentions: A consumer socialization framework. Journal ofÂ  Interactive Marketing, 26(4), 198-208.Â Wang, Putri, Christianto, & W, (2019). An empirical examination of characteristicsÂ Â Â Â Â Â Â Â Â Â Â  of mobile payment users in Indonesia inâ€‚Journal ofÂ Â Â Â Â Â Â Â  Theoretical andÂ Â Â Â Â Â Â Â Â  Applied Information Technology 97(1):169-182Warren J Keagan., Moriarty, Sandara E., Thomas Duncan R. (1995). Marketing (3rd).Â Â Â Â Â Â  NewJersey : Prentice Hall International Inc.Â Wild, Fridolin; Ullmann, Thomas; Scott, Peter; Rebedea, Traian and Hoisl, Bernhard (2011). Applicability of the technology acceptance model for widget basedÂ Â  personal learning environments. In: 1st Workshopon ExploringÂ Â Â Â Â Â Â  Fitness and Evolvability of Personal Learning Environments (EFEPLEâ€™11)Wong, D. (2017).Â  Pengaruh Ability, Benevolence Dan Integrity Terhadap Trust,Â Â  Serta Implikasinya Terhadap Partisipasi Pelanggan E-Commerce: StudiÂ  Kasus Pada Pelanggan E-Commerce Di UBM. Jurnal Riset Manajemen danÂ Â Â Â Â Â Â Â Â Â  Bisnis FE-UNIAT, 2(2), 155-168Yu Zhonggen and Yu Xiaozhi (2019). Departement of English Studies, faculty of Â Â Â Â Â Â Â Â Â Â Â  foreign studies, Beijing language and culture university, Beijing, China. 2Â Â Â Â  March 2019Â Â